(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
The article examines the impact of population size on the choice of technological solutions for the treatment of urban wastewater (UW). It analyzes the factors that determine the specific challenges of wastewater management in cities of different sizes, including the volume and composition of wastewater, regulatory requirements for the quality of treated water, and economic constraints. Based on a comparative analysis, the article provides recommendations for selecting optimal technological schemes and equipment for cities with different populations, ensuring the achievement of required environmental performance and economic efficiency.